2021
DOI: 10.4062/biomolther.2020.227
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Increases Anti-Inflammatory Efficacy of Rectal 5-Amino Salicylic Acid Administration in a Murine Colitis Model

Abstract: 5-amino salicylic acid (5-ASA) is a standard therapy for the treatment of mild to moderate forms of inflammatory bowel diseases (IBD) whereas more severe forms involve the use of steroids and immunosuppressive drugs. Hyaluronic acid (HA) is a naturally occurring non-sulfated glycosaminoglycan that has shown epithelium protective effects in experimental colitis recently. In this study, both 5-ASA (30 mg/kg) and HA (15 mg/kg or 30 mg/kg) were administered rectally and investigated for their potential complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies suggest that structural conformation of HA allows it to form hydrogen bonds or electrostatic interactions with mucin proteins, thus imparting mucoadhesive properties (Figure A). On the other hand, P­(NIPAM) is known to serve as a coating material at physiological temperatures.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies suggest that structural conformation of HA allows it to form hydrogen bonds or electrostatic interactions with mucin proteins, thus imparting mucoadhesive properties (Figure A). On the other hand, P­(NIPAM) is known to serve as a coating material at physiological temperatures.…”
Section: Resultsmentioning
confidence: 97%
“…Although recent studies have demonstrated the possible protective and anti-inflammatory role of HA during colitis [ 19 ], in our experimental conditions, this was not evident, and HA alone did not show any significant amelioration for the severity of colitis in vivo and in ex vivo experiments. Moreover, it has recently been demonstrated that intrarectal HA’s co-administration with Acetylsalicilic acid (ASA) is a very interesting approach to improving the course of colitis [ 20 ]. However, it is important to note that the studies mentioned have employed significantly higher dosages and more frequent administration compared to our experimental plan.…”
Section: Discussionmentioning
confidence: 99%
“…This medicine contributes to the removal of reactive oxygen species generated by inflammation and suppresses the production of leukotrienes, which are involved in inflammation 11,12 . Its combination with natural ingredients has also been studied, and the effect is enhanced when combined with hyaluronic acid and extracts of Glycyrrhiza inflata 13–15 . However, it was reported that 5‐ASA may be inactivated by acetylation through acetyltransferases possessed by certain intestinal bacteria 16 .…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Its combination with natural ingredients has also been studied, and the effect is enhanced when combined with hyaluronic acid and extracts of Glycyrrhiza inflata . 13 , 14 , 15 However, it was reported that 5‐ASA may be inactivated by acetylation through acetyltransferases possessed by certain intestinal bacteria. 16 Therefore, regulation of the intestinal microbiota is important to maximize the effects of 5‐ASA.…”
Section: Introductionmentioning
confidence: 99%